Shakespeare and the Fall of the Roman Republic : Selfhood, Stoicism and Civil War - Gray, Patrick, 1978- (Edinburgh critical studies in Shakespeare and philosophy., 2018)
Shakespeare and the Fall of the Roman Republic introduces Shakespeare as a historian of ancient Rome alongside figures such as Sallust, Cicero, St Augustine, Machiavelli, Gibbon, Hegel and Nietzsche.